Iatrogenic Inflammatory Fibrosis of Hard Palate in a 13-Year-Old Female Patient - Shanthan Mettu; Radhika Muppa; G. Siva Prasad Reddy; Srinivas Nallanchakrava; Sri Veda Gurugubelli (Hindawi Limited, 2013)
Palatal swellings are rare in children and the incidence differs from that of the adult counterparts. When the palatal swellings do arise in children, they usually are palatal abscess from periapical region, and few cases like pleomorphic adenoma in young adults have also been reported. But inflammatory fibrosis of palate in children is a rare occurrence. Inflammatory fibrosis is formation of excess fibrous connective tissue in an organ or tissue, as a reparative or reactive process. This report describes an unusual case of iatrogenic inflammatory fibrosis on the palate due to extraction of tooth number 22 in a 13-year-old female patient. The patient presented with a single large well-circumscribed oval palatal swelling that was soft, fluctuant, not fixed, and nontender. Surgical excision of the lesion was done and it was sent for histopathological assessment. The biopsy showed fibrous tissue with collagen fibers, spindle shaped fibroblasts, neovascularization, RBCs, chronic inflammatory cells, and traces of salivary gland and nerve tissue.